New perspectives on the regulation of iron absorption via cellular zinc concentrations in humans. Issue 10 (3rd July 2017) - Knez, Marija; Graham, Robin D.; Welch, Ross M.; Stangoulis, James C. R.
Abstract: Iron deficiency is the most prevalent nutritional deficiency, affecting more than 30% of the total world's population. It is a major public health problem in many countries around the world. Over the years various methods have been used with an effort to try and control iron-deficiency anemia. However, there has only been a marginal reduction in the global prevalence of anemia. Why is this so? Iron and zinc are essential trace elements for humans. These metals influence the transport and absorption of one another across the enterocytes and hepatocytes, due to similar ionic properties. This paper describes the structure and roles of major iron and zinc transport proteins, clarifies iron-zinc interactions at these sites, and provides a model for the mechanism of these interactions both at the local and systemic level. This review provides evidence that much of the massive extent of iron deficiency anemia in the world may be due to an underlying deficiency of zinc. It explains the reasons for predominance of cellular zinc status in determination of iron/zinc interactions and for the first time thoroughly explains mechanisms by which zinc brings about these changes.